Rekayasa Software Computer Aided Process Planning Berbasis Metode CBR Untuk Membantu Proses Pembuatan Batik - Rahman, Arif; Setyanto, Nasir Widha; Sulistyarini, Dwi Hadi; Arifianto, Endra Yuafanedi; Dewi, Wieke Rossaria; Supangat, Syahrir Aditya (Rekayasa Mesin, 2012)
If we make batik manually, it will less effective and efficient.besides that can make worker uncomfortable. Because the new worker must learn all over again to be a reliable process planner as his predecessor. This is loss to the company. Fortunately there is a method called Computer Aided Process Planning (CAPP). CAPP can use to make job more fast than before. Besides that it will make more effective and efficient plan process.Keywords: Batik, CAPP, CBR